Unveiling Chinese EFL Teachers' Perspectives on Implementing a Play-Based Approach to Phonics Instruction - Yating Qu; Princess Policarpio (Ilmu Inovasi Nusantara, 2025)
This study explores Chinese English as a Foreign Language (EFL) teachers' perspectives on employing a play-based approach in teaching phonics. The case study method will be employed by this study, which is particularly suitable for this research as it allows for an in-depth exploration of the complex, contextualized experiences of Chinese EFL teachers using play-based approaches in phonics instruction. The study captures teachers' perspectives by employing in-depth interviews and classroom observations, thus providing rich, qualitative data that reveals what they do and why and how they integrate play-based methods into their teaching. By analyzing interview and observational data, the study aims to identify significant themes and variations in the teachers' perspectives to enhance phonics learning among their students. Understanding these aspects will provide valuable insights into how play-based learning can effectively adapt to the Chinese EFL context, potentially improving phonics instruction and student outcomes. Finally, the conduct of this study is justified as phonics is essential for developing early reading skills in EFL learners. However, traditional methods may not fully engage students or address their diverse needs. Play-based learning, which emphasizes interactive and enjoyable activities, offers a potential solution by making phonics instruction more engaging and effective